Design of hazard identification system for aircraft power supply system based on SIMPLORER and MATLAB co-simulation. (September 2020) - Zhou, Di; Zhuang, Xiao; Huang, Yan; Cai, Jing; Zuo, Hongfu
The aircraft power supply system provides power for all the electrical equipment on the aircraft. Its normal operation is the key to ensure the safe flight of the aircraft. So, identifying the hazards in aircraft power supply system is necessary and critically important. In this paper, a hazard identification system for APSS based on the combined simulation of SIMPLORER and MATLAB is proposed. First, the different main fault modes in the aircraft power supply system are set on the control interface. Then, through the simulation model established on SIMPLORER, the aircraft power supply system power supply logic simulation is realized in the set fault mode. Finally, the simulation result is sent to the MATLAB to complete an identification process by using support vector machine method. The final state of each component and the identification result are shown in the control interface. The hazard identification system proposed in this paper has strong data interactivity and it can be applied to online hazard identification.